2013
DOI: 10.1089/jop.2013.0146
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Evaluation of 1.5% Levofloxacin Ophthalmic Solution in Ophthalmic Perioperative Disinfection

Abstract: For ophthalmic perioperative disinfection, the LVFX 1.5% ophthalmic solution showed a good safety profile, and critical eradication of gram-positive cocci, including the fluoroquinolone-resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…According to Chojnacki et al, the rifampin plus polymyxin B-trimethoprim combination demonstrated synergistic antimicrobial activity towards ocular clinical Staphylococcus aureus and Pseudomonas aeruginosa isolates, a low spontaneous resistance frequency, and in vitro bactericidal kinetics and antibiofilm activities equal to or exceeding those of moxifloxacin [ 64 ]. Compared to literature on the clinical effects of other antibiotics (Table 8 ), our study revealed a higher sensitivity of conjunctival sac bacteria towards rifampin[ 7 , 65 75 ]. Further, there was not enough evidence for side effects of the topical application of rifampin at low concentrations.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…According to Chojnacki et al, the rifampin plus polymyxin B-trimethoprim combination demonstrated synergistic antimicrobial activity towards ocular clinical Staphylococcus aureus and Pseudomonas aeruginosa isolates, a low spontaneous resistance frequency, and in vitro bactericidal kinetics and antibiofilm activities equal to or exceeding those of moxifloxacin [ 64 ]. Compared to literature on the clinical effects of other antibiotics (Table 8 ), our study revealed a higher sensitivity of conjunctival sac bacteria towards rifampin[ 7 , 65 75 ]. Further, there was not enough evidence for side effects of the topical application of rifampin at low concentrations.…”
Section: Discussioncontrasting
confidence: 78%
“…The use of antibiotics is an effective strategy to significantly decrease the incidence of ocular bacterial infections (positive swabs). Among all kinds of antibiotics, levofloxacin (which belongs to quinolones and fluoroquinolones) has been proved to have well-established efficacy and tolerability in the treatment of external ocular infections caused by both Gram-positive and Gram-negative bacteria [6][7][8][9][10][11][12][13]. However, with the widespread use of antibiotics, the resistance rate of bacteria towards antibiotics (including levofloxacin) has gradually increased, which has become a severe threat to public health [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Although quinolones are not the drugs of choice for anaerobic bacteria, previous studies have reported that P. acnes is susceptible to both moxifloxacin and levofloxacin, which have eradication rates of 76.9%;82.4%. 19,20 In our study, most of the patients (13/16) were initially started on treatment with either moxifloxacin or gatifloxacin. There is an ongoing concern about increased fluoroquinolone-resistant bacteria and imperfect eradication.…”
Section: Discussionmentioning
confidence: 96%
“…Suzuki et al [22] showed a high efficacy of topical use of levofloxacin 1.5%. Eradication rate of conjunctival sac after use of that drug from 3 days before till 14 days after cataract surgery was as follow: for total microbes 86.7%, for CNS 100%, and for Propionibacterium acnes 78.3%).…”
Section: Key Pointsmentioning
confidence: 99%